2022
DOI: 10.33448/rsd-v11i16.38227
|View full text |Cite
|
Sign up to set email alerts
|

Same-sex parenting in Brazil and Portugal: An integrative review

Abstract: This integrative review aimed to analyze and systematize the knowledge produced on parenting by same-sex couples in the Brazilian and Portuguese contexts until 2019. We sought to describe the main topics in scientific production in empirical articles in both countries and highlight advances and/or gaps in the discussions. The databases searched were LILACS, Redalyc, RCAAP, PePSIC, SciELO and EBSCOhost. The searches occurred in 2020, with seven descriptors in Portuguese and their respective translations into En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
2
0
3
Order By: Relevance
“…O primeiro deles foi no Google Acadêmico (https:// scholar.google.com.br), no dia 10 de agosto de 2023. Nesse levantamento, definindo o período de 2020 a 2023, foram identificadas seis revisões [20][21][22][23][24][25][26] . O segundo levantamento foi realizado no Portal Regional da BVS (https://bvsalud.org), no dia 18 de agosto de 2023, sem filtro de ano para a busca.…”
Section: A Produção Científica Da Saúde Em Focounclassified
See 2 more Smart Citations
“…O primeiro deles foi no Google Acadêmico (https:// scholar.google.com.br), no dia 10 de agosto de 2023. Nesse levantamento, definindo o período de 2020 a 2023, foram identificadas seis revisões [20][21][22][23][24][25][26] . O segundo levantamento foi realizado no Portal Regional da BVS (https://bvsalud.org), no dia 18 de agosto de 2023, sem filtro de ano para a busca.…”
Section: A Produção Científica Da Saúde Em Focounclassified
“…No que se refere ao contexto da análise, a maioria das revisões leva em conta tanto a produção nacional quanto a internacional. Como exceção, identificamos uma revisão que focaliza o contexto brasileiro 28 e outra estabelece comparações entre os contextos brasileiro e português 20 .…”
Section: A Produção Científica Da Saúde Em Focounclassified
See 1 more Smart Citation
“…br) on August 10, 2023. This survey identified six reviews [20][21][22][23][24][25][26] in the 2020-2023 defined period. The second survey was run on the BVS Regional Portal (https://bvsalud.org) on August 18, 2023, without a search year filter, and identified four other reviews 4,[26][27][28] , one of which had already been found in the first survey 24 .…”
Section: Scientific Health Production In Focusmentioning
confidence: 99%
“…One study focuses on gay people's family issues 25 . When the LGBT community is mentioned in the texts, they mainly appear as support to homoparental families [20][21][22] .…”
Section: Scientific Health Production In Focusmentioning
confidence: 99%